IMPLEMENTASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN TEMATIK KELAS III SDIT DARUL HASAN PADANGSIDIMPUAN - Asriana Harahap (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
AbstractThis study aims to describe the implementation of character values in thematic learning, character values developed and find out the supporting factors and inhibiting factors for the implementation of character values in class III SDIT Darul Hasan Padangsidimpuan thematic learning.This study uses a qualitative approach with descriptive types. The research subjects were class III students and homerooms and principals to support the data. This research was conducted at SDIT Darul Hasan Padangsidimpuan in the odd semester of the 2017/2018 academic year. Data collection techniques used by observation, interviews and documentation. Data analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. Data validity technique with source and technique triangulation.The results of the study show that the implementation of character values includes planning and implementation. In planning learning consists of syllabus from the service / government and RPP made by the teacher. Whereas in its implementation, the teacher in implementing character values through learning activities and methods of learning, assessment, discipline, discipline, habituation and example. Character values developed by the teacher in thematic learning character values are obtained which often appear values of other characters that rarely appear. The main supporters in the implementation of character values are school through activities and facilities, teachers through exemplary, learning strategies, media and learning resources. The inhibiting factor is the environment, students and time. Keywords: Implementation, Character Values, Thematic Learning.